Collagen imaging in human intracranial aneurysms: a translational proof-of-concept study - Hackenberg, Katharina; Willett, Nicola; Seibold, Uwe; Weingarten, Gereon; Dreier, Rita; Pantelic, Natalija; Abdulazim, Amr Nabil; Rinkel, Gabriel J. E.; Wängler, Björn; Wängler, Carmen; Etminan, Nima (Translational stroke research, 2026)
Unruptured intracranial aneurysms (IAs) are highly prevalent in the general population and there is an unmet need for radiological surrogates for the assessment of an increased risk of rupture. High turnover of type I collagen, i.e. abundant proportions of newly synthesized, immature collagen, has been linked to structural instability of the IA wall. This study aimed to test a newly synthesized positron emission tomography tracer that could selectively visualize immature type I collagen in human IAs as a marker for structural instability and thereby increased rupture risk. Following the synthesis of [68Ga]Ga-NODA-GA-PEG1-collagelin, in vitro and ex vivo analyses of collagen, nonhuman tissue and human IAs were performed. Patients undergoing microsurgical repair for unruptured and ruptured IAs were prospectively included in this cross-sectional, single-center study. After safe IA clipping and IA excision, cryosections of IAs were incubated with the tracer, and signal intensity was quantified via autoradiography. To differentiate immature from mature collagen, polarization microscopy was performed after picrosirius red staining. Our study showed that the synthesized tracer [68Ga]Ga-NODA-GA-PEG1-collagelin bound specifically to type I collagen in vitro and in rat tail tendon ex vivo. We included 25 patients with 25 IAs (12 unruptured, 13 ruptured). The tracer preferentially labeled immature type I collagen in human IAs ex vivo: Regions with high tracer uptake correlated with areas rich in immature collagen, as identified by polarization microscopy (r = 0.40, P = 0.002). [68Ga]Ga-NODA-GA-PEG1-collagelin could serve as a complementary, noninvasive molecular imaging tool for personalized assessment of IA instability, but animal studies are required before in vivo use of [68Ga]Ga-NODA-GA-PEG1-collagelin in humans.